2021
DOI: 10.1177/2333794x211023711
|View full text |Cite
|
Sign up to set email alerts
|

Bullying as a Risk Factor of Depression on Undergraduate Health Students

Abstract: Depression is a serious health problem that needs to be treated early so that it does not get worse in the future. Bullying can cause a mental health problem on students. This study aims to analyze the relationship between bullying and depression among undergraduate health students. This was an observational study with a cross-sectional design. Respondents filled out questionnaires online using the Google Form application. A total of 246 undergraduate health students participated in this study. Multivariate lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Also, bullying among students has been reported as a common cause of depression to the victims since it affects their self-esteem and image leading to social withdrawal, feelings of sadness and hence depression. [32][33][34] Unlike ndings from other studies conducted during COVID-19 pandemic which found that being a nal year student was protective against depression, there was no signi cant association between depression and year of study 6,23 . This could be because COVID-19 and the associated lockdown affected most people non-selectively regardless of the student's year of study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, bullying among students has been reported as a common cause of depression to the victims since it affects their self-esteem and image leading to social withdrawal, feelings of sadness and hence depression. [32][33][34] Unlike ndings from other studies conducted during COVID-19 pandemic which found that being a nal year student was protective against depression, there was no signi cant association between depression and year of study 6,23 . This could be because COVID-19 and the associated lockdown affected most people non-selectively regardless of the student's year of study.…”
Section: Discussionmentioning
confidence: 99%
“…Setiadi et al [ 50 ] analyzed the relationship between bullying and depression among undergraduate health students and found an association between bullying and the incidence of depression. Another study by Martínez-Monteagudo et al [ 51 ] reported that being a cyberbullying victim increases the probability of suicidal thinking and leads to high levels of depression, anxiety, and stress.…”
Section: Discussionmentioning
confidence: 99%
“…Also in accordance with research by Tristanti et al (2020) (12), some problems are more likely to be suffered by children who are victims of bullying, including the emergence of various mental health problems, such as depression, anxiety, and sleep problems which may be carried over into adulthood, physical health complaints, feelings of being unsafe in the school environment, as well as decreasing enthusiasm for learning and academic achievement. The psychological impact that occurs on victims as a result of bullying, namely being mentally down, not being enthusiastic about going to school, anxiety disorders, prolonged depression, feeling like you have no self-esteem and no self-confidence (13)(14)(15).…”
Section: Behavioral Evaluation or Impactmentioning
confidence: 99%